Development of a tablet application for the screening of receptive vocabulary skills in multilingual children: A pilot study. (June 2016) - Schaefer, Blanca; Bowyer-Crane, Claudine; Herrmann, Frank; Fricke, Silke
For professionals working with multilingual children, detecting language deficits in a child's home language can present a challenge. This is largely due to the scarcity of standardized assessments in many children's home languages and missing normative data on multilingual language acquisition. A common approach is to translate existing English language vocabulary measures into other languages. However, this approach does not take into account the cultural and linguistic differences between languages. This pilot study explored whether English and home-language receptive vocabulary skills can be objectively and reliably screened using a tablet application. Preliminary data on monolingual and multilingual vocabulary skills was collected from 139 children aged 6–7 years. A tablet application was designed to assess children's receptive vocabulary in both English and an additional eight languages using a four-choice picture paradigm. Linguistically controlled and pre-recorded target items are presented orally via the tablet in each language and responses are made via the touch screen and are automatically scored. The English version of the test was administered to 67 monolingual and 72 multilingual children, while 38 multilingual children also completed the test in their home language. Test criteria measures, including reliability and concurrent validity showed satisfactory results. These findings suggest that the tablet application could be a useful tool for professionals to screen receptive vocabulary skills in monolingual and multilingual children. Limitations of the first version of the receptive vocabulary screener and future steps are discussed.